Effect of Intraocular Forward Scattering and Corneal Higher-Order Aberrations on Visual Acuity after Descemet’s Stripping Automated Endothelial Keratoplasty - Kamiya, Kazutaka (PLoS One, 2015)
PURPOSE: To assess the relationship of intraocular forward scattering and corneal higher-order aberrations (HOAs) with best spectacle corrected visual acuity (BSCVA) after Descemet’s stripping automated endothelial keratoplasty (DSAEK), and to compare these parameters between DSAEK and non-Descemet’s stripping automated endothelial keratoplasty (n-DSAEK) groups. METHODS: This retrospective study enrolled thirty eyes of 30 consecutive patients who underwent standard DSAEK, and who underwent successful phacoemulsification with intraocular lens implantation before DSAEK. The mean age at the time of surgery was 71.7 ± 10.4 years. We quantitatively evaluated the objective scattering index (OSI) using the double-pass instrument (OQAS II, Visiometrics) and corneal HOAs using Hartmann-Shack aberrometry (KR-9000PW, Topcon) 3 months postoperatively. RESULTS: The mean OSI, corneal HOAs, and logMAR BSCVA 3 months after DSAEK were 7.91 ± 3.58, 0.43 ± 0.27 μm, and 0.32 ± 0.25, respectively. We found a significant correlation between the OSI and logMAR BSCVA (Spearman correlation coefficient r=0.714, p<0.001), but no significant association between corneal HOAs and logMAR BSCVA 3 months postoperatively (r=0.209, p=0.267). We found no significant differences in any postoperative parameters between the DSAEK and n-DSAEK groups (p>0.05). CONCLUSIONS: Our pilot study demonstrated that the postoperative corrected visual acuity was significantly correlated with intraocular forward scattering, but not with corneal HOAs in post-DSAEK eyes, suggesting that intraocular forward scattering plays a more essential role in postoperative visual performance than corneal aberrations after DSAEK. The detailed visual performance, such as HOAs and intraocular scattering, after n-DSAEK appears to be essentially equivalent to that after DSAEK.